Pan African strategy for the progressive control of peste des petits ruminants (Pan African ppr strategy) - Elsawalhy, A.; Mariner, Jeffrey C.; Chibeu, D.; Wamway, H.; Wakhusama, S.; Olaho-Mukani, W.; Toye, Philip G. (2010)
Peste des petits ruminants (PPR) is a major constraint to the livelihoods and food security of small scale farmers. The epidemiology and biology of PPR virus has much in common with rinderpest virus (RP), an agent that has been globally eradicated. This document presents a strategy for the progressive control of PPR that builds upon the lessons learnt from rinderpest eradication. Progressive control relies upon a modular approach that consists of a series of self-sufficient phases each with its own set of sustainable results. Key intermediate results will be proven business models for sustainable PPR control service delivery and enhanced capacity of animal health institutions to target control services to critical control points. The program will foster an adaptive management approach that integrates learning approaches to drive animal health institutional innovation. The coordinated drive towards long term animal health goals will add value to on-going investments in infectious disease control.